A Critical Study on Portfolio Optimization of Physical Gold and its Derivatives as an Ideal Investment Choice - Das, Chandrima (Indian Journal of Finance, 2010)
It is known that Physical Gold has been always the craze among investors for investment to hedge against inflation and to fight against risk involved due to different economic conditions. The sparkling metal has always been in a stable /boom state in spite of stock market crash or economic inflation /recession. But with needs of the investors' changing, the Financial Innovators are trying to attract the investors by floating the same in varied forms .The resultant is Gold Futures and Gold ETF. Also, with the listing of one of the Gold Mining Company (Deccan Gold Mines Limited) in both the Indian Stock Exchanges, there is also an increasing chance of investors to invest in the stock of Deccan Gold. The advantage of this is that rather than investing solely in Physical gold, one can create a portfolio of Physical Gold, Gold Stock, Gold Futures and Gold ETF to enjoy the benefits of each product and try to prevent the odds attached to each. Each of the products has its own advantages and disadvantages, so forming an ideal portfolio which can give good handsome return in different economic condition is the main idea behind the paper. The paper finally ends with the conclusion that it is better to invest in Gold ETF as a separate instrument instead of mixing with other forms of gold in the form of portfolio. An ideal portfolio should consist of Physical gold, gold stock and Gold Futures.